Recruitment Behaviour in an African Meliponine Bee Species (hymenoptera, Apidae: Meliponini): Understanding Glandular Origin and Pheromonal Components - Bobadoye, Bridget O.; Alamu, Olaniyi T.; George-Onaho, Jennifer A.; Ete, John A.; Ayandokun, Ayangbade E.; Agboola, Ifeoluwa S.; Adeoye, Olubusola T.; Adekola, Popoola J. (Tanzania Journal of Science, 2023)
Meliponine bees are speculated to use a variety of communication mechanisms to effectively recruit workers of a colony to collect sufficient amounts of food to nourish the entire nest population. Mechanisms used to convey such information include thoracic vibrations and trophallaxis within the nest; footprint secretions and pheromone marks deposited in the field, or a combination of these signals and cues. There have been numerous discrepancies about the origin of trail pheromone production from the head, thorax, abdomen and leg regions of meliponine bees. Because the glandular origin of pheromone marks deposited by African meliponine bee’s species has not yet been investigated, we first confirmed if these species actually carry out scent marking and recruitment behaviour at visited food sources. Secondly, we tested if either nasonov or tarsal gland secretions elicited trail-following behaviour in newly recruited bees by means of chemical and electro-physiological analyses as well as with bio-assays testing both natural extracts and synthetic pheromone compounds from both glands. Significant differences were observed in the foraging patterns of the four bee species on collected resources (nectar, pollen and water) as the synthetic compound, (E)-β-farnesene was significantly as attractive to foragers of the four species when compared to the natural nasonov gland extract. Our results showed a significantly higher proportion of foragers from the four species been attracted to food resources baited with natural extracts from their own glands and recruited additional foragers to such baited food sites. Keywords: Meliponine bee species, recruitment behaviour, nasonov glands, tarsal glands